PERAN POS BANTUAN HUKUM (POSBAKUM) DI PENGADILAN AGAMA BENGKULU KELAS I A BERDASARKAN PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2014 - Prabowo, Ari (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
The purpose of this research is to know  the  Role of Post  of Legal Aid (Posbakum) based on Supreme Court Regulation  Number  1 Year 2014 and  implementation of Posbakum in serving  the  justice  seeking society  that  can  not afford in Religious Court of Bengkulu  Class I A. Research conducted at Bengkulu  City Court, at March-June  2017. The research method used  is survey method and data retrieval technique done  by library study and open  interview. Data were analyzed  descriptively  qualitative.  The result of this research is expected to have social value which  is giving information to Bengkulu people in particular,  and society (nation) Indonesia generally about  the benefits  or the power  of Legal Aid to the poor people in Religious Court of Bengkulu Class I A.